Engineered cellular carrier nanoerythrosomes as potential targeting vectors for anti-malarial drug - Agnihotri, Jaya; Gajbhiye, Virendra; Jain, Narendra Kumar (Asian Journal of Pharmaceutics (AJP), 2014)
The present investigation was aimed at developing and exploring the use of nanoerythrosomes (nEs) for targeted delivery of anti-malarial drug, pyrimethamine (PMA). The formulation was prepared by the extrusion method and drug was conjugated to nEs with the help of gluteraldehyde used as a cross-linking agent. The nEs formulation was optimized for drug concentration, surface morphology, viscosity, and sedimentation volume. The drug-loaded nEs showed delayed in vitro release, good stability at 4±1°C, and controlled in vivo release. Tissue distribution studies showed higher accumulation of drug in liver (17.34±1.3 μg/ml) at 3 h in the case of nEs as compared to free drug (12.82±0.7 μg/ml). A higher amount of drug i.e. 13.14±0.9 μg/ml was found after 24 h in liver in the case of nEs as compared to free drug concentration of 9.72±0.5 μg/ml. Data showed that developed PMA-loaded nEs hold promise for targeting and controlling the release of drug and improve treatment of malaria.